2006
DOI: 10.1016/j.reprotox.2006.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry evaluation of lead and cadmium effects on mouse spermatogenesis

Abstract: Flow cytometry (FCM) is a powerful tool to evaluate cell DNA content and ploidy levels. We have assessed the accuracy of two protocols of nuclei isolation from paraffinized samples (P1 and P2) by comparing FCM results with those obtained using fresh material (F1-F3). After isolation, nuclei were stained with propidium iodide and quantitatively analysed by FCM for changes in germ cell ratios. Results obtained with Protocol P2 were similar to those obtained using the protocol that gave best results for fresh tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 24 publications
3
23
0
Order By: Relevance
“…Similar result was obtained by Oliveira et al (2006). The decreased sperm motility in Cd-treated rats could be attributed to the ability of Cd to bind with calmodulin instead of calcium inhibiting its role in sperm motility (Schlingmann et al 2007).…”
Section: Discussionsupporting
confidence: 74%
“…Similar result was obtained by Oliveira et al (2006). The decreased sperm motility in Cd-treated rats could be attributed to the ability of Cd to bind with calmodulin instead of calcium inhibiting its role in sperm motility (Schlingmann et al 2007).…”
Section: Discussionsupporting
confidence: 74%
“…Previous work from our laboratory, investigating the effects of lead chloride (at 74 e 100 mg PbCl 2 /kg bw) on mouse spermatogenesis, showed an increase in the percentage of cells in S-phase, suggesting that this compound might have a mitogenic effect (Oliveira et al 2006). In this context, spermatogenesis and sperm function could also be affected by exposure to these concentrations of lead.…”
Section: Discussionmentioning
confidence: 73%
“…The subcutaneous route was selected since it allows a slow absorption of lead and allows a higher control of the experiment and has been previously used in other studies with lead (Graça et al 2004;Oliveira et al 2006) and other metals [e.g. cadmium (Zhou et al 2004)].…”
Section: Animals and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Adhikari et al [1] also reported that Pb could induce apoptosis in the germ cells within the semineferous tubules. Although adverse effects of lead compounds on the testis have long been studied [5] , effective drugs reversing the toxicity of lead on male reproduction are still scarce and insufficient.…”
Section: The Protective Effect Of Ascorbic Acid and Thiamine Supplemementioning
confidence: 99%